Preferensi Pengembangan Permukiman Pusat Kota di Kelurahan Pandansari, Kecamatan Semarang Tengah, Kota Semarang - Fahdian, Achmad Tsani; Mardiansjah, Fadjar Hari (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
The less settlements, especially in urban settlements, urban regeneration is needed to support the preparation of residential land. The purpose of this study is to determine the preferences of the development of residential areas located downtown if influenced by internal and external factors that exist around the area. The research method used in this study is quantitative-qualitative mix method, with survey technique and descriptive statistical analysis using cross-sectional (crosstab) and chi-square test. The result of the research shows that the better education level with the old age with the status of HGB occupancy, Pandansari residents mostly have non-permanent job and utilize occupancy to trade. For residential characteristics, one floor functioned as a private residence, while 2 floors for residence kos, there are also in the form of shophouses, inns, hotels, and even there is an apartment being built. Residential preference of Pandansari residents to their present occupancy of shelter, safe environment of flood, tranquility, and hygiene, good drainage condition, effectiveness of water quality provision, electricity supply, good quality of educational facilities, and proximity to trading facilities. Implementation of the concept of city cluster development can be done if: equal land area, model model house, community access road, fair tax policy between landowners, controlled population density, fair management cooperation with investors, economic improvement, and the common vision of residents.